2016
DOI: 10.1073/pnas.1611509113
|View full text |Cite
|
Sign up to set email alerts
|

Emergent oscillations assist obstacle negotiation during ant cooperative transport

Abstract: Collective motion by animal groups is affected by internal interactions, external constraints, and the influx of information. A quantitative understanding of how these different factors give rise to different modes of collective motion is, at present, lacking. Here, we study how ants that cooperatively transport a large food item react to an obstacle blocking their path. Combining experiments with a statistical physics model of mechanically coupled active agents, we show that the constraint induces a determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 30 publications
(53 reference statements)
4
36
0
Order By: Relevance
“…Obstacle navigation may pose substantially different challenges than initiating movement, in part because the group must decide on a new travel direction when the preferred direction is unavailable. Several other studies have been published on obstacle navigation during cooperative transport by P. longicornis (Fonio et al, 2016;Gelblum et al, 2016;McCreery et al, 2016b;Ron et al, 2018), focusing primarily on navigation dynamics and the mechanisms that allow groups to successfully move around complex obstacles. Rather than further examining these mechanisms, we instead focused on how object properties affect the performance of groups as they progress through the obstacle navigation process.…”
Section: Performance During Obstacle Navigation (Transport Phase)mentioning
confidence: 99%
“…Obstacle navigation may pose substantially different challenges than initiating movement, in part because the group must decide on a new travel direction when the preferred direction is unavailable. Several other studies have been published on obstacle navigation during cooperative transport by P. longicornis (Fonio et al, 2016;Gelblum et al, 2016;McCreery et al, 2016b;Ron et al, 2018), focusing primarily on navigation dynamics and the mechanisms that allow groups to successfully move around complex obstacles. Rather than further examining these mechanisms, we instead focused on how object properties affect the performance of groups as they progress through the obstacle navigation process.…”
Section: Performance During Obstacle Navigation (Transport Phase)mentioning
confidence: 99%
“…Lastly, the simulation results revealed that stochastic force generation, whether 311 generated coincidentally by friction with the ground or intrinsically by the 312 system [11,12], can also assist in navigating more complicated obstacles. The success 313 rate could be further enhanced by using an informed-ant-attachment mechanism [3].…”
mentioning
confidence: 98%
“…The speed is simply proportional 218 to group size in P. longicornis [11,12]. It is proportional at small group size and then 219 becomes saturated at large group size in the neotropical ants Pheidole oxyops [21] and 220 Aphaenogaster cockerelli [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations